Environmental modelling of aluminium based components manufacturing routes: Additive manufacturing versus machining versus forming. (1st March 2018) - Ingarao, Giuseppe; Priarone, Paolo C.; Deng, Yelin; Paraskevas, Dimos
Abstract: Additive Manufacturing represents, by now, a viable alternative for metal-based components production. Therefore the designer, often, has to select among three options at process design stage: subtractive, mass conserving, and additive approaches. The selection of a given process, besides affecting the manufacturing step impact, influences significantly the impact related to the material production step. If the process enables a part weight reduction (as the Additive Manufacturing approaches do) even the use phase is affected by the manufacturing approach selection. The present research provides a comprehensive environmental manufacturing approaches comparison for components made of aluminum alloys. Additive manufacturing (Selective Laser Sintering), machining, and forming processes are analyzed and compared by means of Life Cycle Assessment techniques. The effect of weight reduction enabled by additive approach is considered. The paper aims at highlighting the strong link between manufacturing approach selection and material use. In this respect, a thorough environmental analysis of the pre-manufacturing step is developed. Moreover, the influence of eco-attributes aluminium variability on the comparative analysis results is studied. The paper, therefore, contributes to the development of a methodology for manufacturing approaches comparison, providing guidelines for green manufacturing approach selection. Results reveal that, for the analyzed case studies, the Additive Manufacturing is a sustainable solution for aluminium components only under a specific scenario: high complexity shapes, significant weight reduction, and application in transportation systems. Highlights: Environmental manufacturing routes comparison for parts made of aluminum alloys. Selective Laser Melting vs. machining vs. forming. A thorough environmental analysis of the pre-manufacturing step is presented. The variability of aluminum eco-attributes is analyzed. For the analyzed case studies, AM is a green choice only for specific applications.